Current collector and preparation method thereof, electrode and secondary battery

Through the dry film making process, the electrolyte material is combined with conductive material and bonding material, which solves the problem of uneven dispersion of solid electrolyte materials and improves the performance of lithium-ion batteries.

CN119864423APending Publication Date: 2025-04-22SHENZHEN BTR NEW ENERGY TECH RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411923722.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The solid electrolyte material powder is prone to uneven dispersion after forming the slurry, which affects the final use effect.

Method used

Through the dry film making process, the electrolyte material, conductive material and bonding material are combined in a dry state to form a self-supporting diaphragm, solving the problem of uneven dispersion of electrolyte materials.

Benefits of technology

Improves the distribution of solid electrolytes and improves its use effect in lithium-ion batteries, including improving the low-temperature performance, rate performance and mechanical safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864423A_ABST
    Figure CN119864423A_ABST
Patent Text Reader

Abstract

The invention discloses a current collector and a preparation method thereof, an electrode and a secondary battery, and the current collector comprises a foil material which is provided with two opposite surfaces; the film layer is attached to at least one surface of the foil; wherein the film layer comprises an electrolyte material, a first conductive material and a first binding material, and the film layer is at least formed by combining the electrolyte material, the first conductive material and the first binding material in a dry state. The current collector, the preparation method thereof, the electrode and the secondary battery have the beneficial effects that the distribution of the solid electrolyte is improved in a dry-method membrane preparation manner, so that the use effect of the current collector is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of secondary batteries, and in particular, relates to a current collector and a preparation method thereof, an electrode and a secondary battery. Background Art

[0002] Solid electrolyte materials such as lithium aluminum titanium phosphate (LATP for short) can be used in lithium-ion batteries to improve the battery's low-temperature performance, rate performance, and mechanical safety performance.

[0003] In some related technologies, there are many different ways to introduce solid electrolyte materials into lithium-ion batteries, such as adding solid electrolyte materials and metallic lithium interfaces to polymer electrolyte membranes for surface modification; using a scraping method to apply a solid electrolyte material dispersion to the surface of a PE diaphragm to form a solid electrolyte material / PE film diaphragm, thereby improving the ion conductivity and thermal stability of the film diaphragm; or using solid electrolyte materials for positive electrode coating technology, which helps to improve the safety, rate and low-temperature performance of the battery cell; or using solid electrolyte materials for electrode blending, which can effectively improve the performance of the battery cell.

[0004] However, the solid electrolyte material powder has a large surface area, so it is easy to be unevenly dispersed after it forms a slurry, thus affecting the final use effect. Summary of the invention

[0005] In view of this, the present application provides a current collector and a preparation method thereof, an electrode and a secondary battery, aiming to solve the aforementioned technical problems.

[0006] As a first aspect of the present application, some embodiments of the present application provide a current collector, the current collector comprising:

[0007] A foil having two surfaces disposed opposite to each other;

[0008] A film layer attached to at least one surface of the foil;

[0009] The membrane layer includes an electrolyte material, a first conductive material and a first adhesive material, and the membrane layer is formed by combining at least the electrolyte material, the first conductive material and the first adhesive material in a dry state.

[0010] Optionally, in some embodiments of the present application, the particle size of the electrolyte material ranges from 200 nm to 500 nm; and / or

[0011] The thickness of the membrane layer is in the range of 4 μm to 12 μm; and / or the ratio of the thickness of the membrane layer to the particle size of the electrolyte material is in the range of 8 to 60; and / or:

[0012] The electrolyte material is lithium titanium phosphate; and / or

[0013] The chemical formula of the electrolyte material is Li 1.4 A l0.4 Ti 1.6 (PO4)3; and / or

[0014] In the membrane layer, the mass percentage of the electrolyte material ranges from 91% to 97.9%.

[0015] Optionally, in some embodiments of the present application, the foil comprises copper metal and / or aluminum metal.

[0016] Optionally, in some embodiments of the present application, the film layer is bonded to the foil by rolling at a first preset temperature.

[0017] Optionally, in some embodiments of the present application, the first conductive material is selected from one or more of conductive carbon black, conductive graphite, carbon nanotubes, and vapor-grown carbon fibers in the film layer; and / or

[0018] The first bonding material is selected from one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polyethylene oxide, polyphenylene ether or polydimethylsiloxane.

[0019] As a second aspect of the present application, some embodiments of the present application provide an electrode comprising the aforementioned current collector.

[0020] Optionally, in some embodiments of the present application, the electrode further comprises:

[0021] The active material layer is attached to the side of the film layer away from the foil.

[0022] Optionally, in some embodiments of the present application, the active material layer is formed by combining its raw materials in a dry state; the active material layer is bonded to the current collector by rolling at a second preset temperature.

[0023] Optionally, in some embodiments of the present application, the active material layer includes: an active material, a second conductive material and a second bonding material.

[0024] Optionally, in some embodiments of the present application, the active material is selected from one or more of natural graphite, artificial graphite, silicon carbon / graphite mixture, silicon oxide / graphite mixture, lithium titanate, hard carbon, soft carbon, activated carbon, lithium battery ternary material, lithium iron phosphate, lithium cobalt oxide, sodium battery layered oxide, sodium battery polyanion compound, sodium battery Prussian blue analogue; and / or

[0025] The second conductive material is selected from one or more of conductive carbon black, conductive graphite, carbon nanotubes, and vapor-grown carbon fibers; and / or

[0026] The second bonding material is selected from one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polyethylene oxide, polyphenylene ether or polydimethylsiloxane.

[0027] As a third aspect of the present application, some embodiments of the present application provide a method for preparing a current collector, including: the method for preparing a current collector includes:

[0028] Providing a film layer;

[0029] Provide foil;

[0030] attaching the film layer to the surface of the foil;

[0031] The membrane layer includes an electrolyte material, a first conductive material and a first adhesive material, and the membrane layer is formed by combining at least the electrolyte material, the first conductive material and the first adhesive material in a dry state.

[0032] Optionally, in some embodiments of the present application, providing a film layer includes:

[0033] The mixed electrolyte material, the first conductive material and the first bonding material are subjected to a fiberizing treatment at a third preset temperature and a preset shearing speed to obtain a fiberized powder;

[0034] The fiberized powder is rolled to obtain the film layer.

[0035] Optionally, in some embodiments of the present application, the third preset temperature ranges from 40°C to 200°C; the preset shear speed ranges from 30m / s to 40m / s.

[0036] Optionally, in some embodiments of the present application, the step of attaching the film layer to the surface of the foil material comprises:

[0037] The film layer is bonded to the surface of the foil by rolling at a fourth preset temperature.

[0038] Optionally, in some embodiments of the present application, the fourth preset temperature ranges from 100°C to 180°C.

[0039] As a fourth aspect of the present application, some embodiments of the present application further provide a secondary battery, which may include: the aforementioned current collector, the aforementioned electrode, and the current collector prepared by the aforementioned preparation method.

[0040] Beneficial effects of the present application: Provided are a current collector and a preparation method thereof, an electrode and a secondary battery that improve the distribution of a solid electrolyte through dry film formation to improve its use effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.

[0042] Figure 1 is a schematic diagram of the structure of electrodes provided in some embodiments of the present application;

[0043] Figure 2 is a schematic structural diagram of a secondary battery provided in some embodiments of the present application;

[0044] Figure 3 A schematic diagram of the main steps of the method for preparing an electrode provided in some embodiments of the present application;

[0045] Figure 4 This is a physical picture of the film layer of Example 2 of the present application after being attached to the aluminum foil;

[0046] Figure 5 It is a comparison diagram of full battery charge and discharge curves of Example 2 and Comparative Example 1;

[0047] Figure 6 It is a comparison diagram of the full battery AC impedance curves of Example 2 and Comparative Example 1.

[0048] Reference numerals: 10, electrode; 11, foil; 12, membrane layer; 13, active material layer; 20, negative electrode; 30, separator; 40, positive electrode. DETAILED DESCRIPTION

[0049] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0050] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0051] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.

[0052] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0053] In the present application, "at least one" means one or more, and "plurality" means two or more. "One or more", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0054] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0055] Reference Figure 1 and Figure 2As shown, the current collector provided in some embodiments of the present application includes: a foil material and a film layer (also referred to as a bottom film layer).

[0056] The foil has two surfaces arranged opposite to each other; the film layer is attached to at least one surface of the foil; the film layer includes an electrolyte material, a first conductive material and a first adhesive material, and the film layer is at least composed of the electrolyte material, the first conductive material and the first adhesive material, and is at least composed of the electrolyte material, the adhesive material and the first conductive material combined in a dry state.

[0057] It should be noted that the dry state in the present application refers to the state in which the ambient temperature is 25°C ± 3°C and the ambient humidity is 0.1% to 5%, and the electrolyte material, the first conductive material and the first adhesive material are all in a dry powder state, that is, a state without any solvent.

[0058] Of course, the film layer can also be attached to both sides of the foil at the same time.

[0059] The above solution combines the electrolyte material and other materials of the membrane layer into a self-supporting membrane through a dry process, thereby avoiding the problem of agglomeration of the electrolyte material in a wet process, thereby affecting the function of the electrolyte material.

[0060] In some embodiments of the present application, the particle size of the electrolyte material in the membrane layer ranges from 200 nm to 500 nm.

[0061] In some embodiments of the present application, the thickness of the film layer ranges from 4 μm to 12 μm.

[0062] In some embodiments of the present application, the thickness of the film layer ranges from any one of 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, and 12 μm, or a range between any two of them.

[0063] In some embodiments of the present application, the ratio of the thickness of the membrane layer to the particle size of the electrolyte material in the membrane layer ranges from 8 to 60.

[0064] In some embodiments of the present application, the chemical formula of the electrolyte material is Li 1.4 Al 0.4 Ti 1.6 (PO4)3.

[0065] In some embodiments of the present application, the foil comprises copper metal and / or aluminum metal.

[0066] In some embodiments of the present application, in the membrane layer, the mass percentage of the electrolyte material ranges from 91% to 97.9%.

[0067] In some embodiments of the present application, the film layer is bonded to the foil by rolling at a first preset temperature.

[0068] In some embodiments of the present application, the first conductive material is selected from one or more of conductive carbon black, conductive graphite, carbon nanotubes, and vapor-grown carbon fibers.

[0069] In some embodiments of the present application, the bonding material is selected from one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polyethylene oxide, polyphenylene ether or polydimethylsiloxane.

[0070] Reference Figure 2 As shown, some embodiments of the present application provide electrodes including the aforementioned current collector and an active material layer. The active material layer is attached to the side of the film layer away from the foil material. That is, the film layer is disposed between the active material layer and the foil material.

[0071] In some embodiments of the present application, the active material layer is formed by combining raw materials thereof in a dry state; and the active material layer is combined to the current collector by rolling at a second preset temperature.

[0072] In some embodiments of the present application, the active material layer includes: an active material, a second conductive material, and a second bonding material.

[0073] In some embodiments of the present application, the active material is selected from one or more of natural graphite, artificial graphite, silicon-carbon / graphite mixture, silicon oxide / graphite mixture, lithium titanate, hard carbon, soft carbon, activated carbon, lithium battery ternary material, lithium iron phosphate, lithium cobalt oxide, sodium battery layered oxide, sodium battery polyanion compound, sodium battery Prussian blue analogue; and / or the second conductive material is selected from one or more of conductive carbon black, conductive graphite, carbon nanotubes, and vapor-grown carbon fiber; and / or the second bonding material is selected from one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polyethylene oxide, polyphenylene ether or polydimethylsiloxane.

[0074] Reference Figure 3 As shown, some embodiments of the present application also provide methods for preparing the aforementioned current collector and electrode. Among them, the method for preparing the current collector is a pre-order step of the method for preparing the electrode, that is, the method for preparing the electrode includes the steps of the aforementioned method for preparing the current collector.

[0075] Specifically, some embodiments of the present application provide a method for preparing a current collector including:

[0076] S100: provides a membrane layer;

[0077] S200: attaching the film layer to a surface of a foil material.

[0078] The membrane layer includes an electrolyte material, a first conductive material and a first adhesive material, and the membrane layer is at least composed of the electrolyte material, the first conductive material and the first adhesive material, and is at least composed of the electrolyte material, the adhesive material and the first conductive material combined in a dry state.

[0079] In some embodiments of the present application, step S100 includes: fiberizing the mixed electrolyte material, the first conductive material and the first adhesive material at a third preset temperature and a preset shear rate to obtain a fiberized powder; and rolling the fiberized powder to obtain the membrane layer.

[0080] In some embodiments of the present application, the third preset temperature ranges from 40°C to 200°C; the preset shear speed ranges from 30m / s to 40m / s.

[0081] In some embodiments of the present application, step S200 includes: bonding the film layer to the surface of the foil by rolling at a fourth preset temperature.

[0082] In some embodiments of the present application, the fourth preset temperature ranges from 100°C to 180°C.

[0083] Reference Figure 3 As shown, some embodiments of the present application provide a method for preparing an electrode including:

[0084] S100: provides a membrane layer;

[0085] S200: attaching the film layer to a surface of a foil;

[0086] S300: attaching an active material layer to the current collector.

[0087] Reference Figure 2 As shown, some embodiments of the present application provide a secondary battery including: the aforementioned electrode or current collector. More specifically, the secondary battery includes: a positive electrode, a negative electrode and a separator. The positive electrode or the negative electrode may adopt the solution of the aforementioned electrode.

[0088] Reference Figure 1 As shown, the electrode of the present application adopts a double-sided structure, that is, the membrane layer and the active material layer are sequentially attached to both sides of the foil.

[0089] Reference Figure 2 As shown, the secondary battery of the present application can be constructed in the order of "double-sided negative electrode sheet-separator-double-sided positive electrode sheet-separator-double-sided negative electrode sheet" to form a full battery.

[0090] In the above scheme, the electrolyte material is introduced into the film layer of the foil by a dry process, and it is determined that when the particle size of the electrolyte material is between 200nm and 500nm, it helps to improve the ionic conductivity of the film layer. At the same time, when the thickness of the film layer is in the range of 4μm to 12μm, that is, when the thickness of the film layer is also in a suitable range, it can ensure that the battery has better electrical performance, which is equivalent to balancing the thickness required for dry film formation and the effect brought by the electrolyte material.

[0091] Because the particle size of the electrolyte material in the battery material is directly related to the diffusion path of ions, the specific surface area, tap density, fluidity and slurry viscosity of the material, which in turn affects the electrochemical performance and processing performance of the battery. The particle size of the electrolyte material used in this application is moderate, which helps to improve the ionic conductivity and electrical performance in the battery.

[0092] In some embodiments of the present application, the particle size of the electrolyte material may range from 200 nm to 500 nm, in order to prevent the prepared LATP dispersion from being unevenly dispersed or even causing slurry sedimentation due to the particle size being too large or too small, thereby affecting the consistency of the electrode.

[0093] In some embodiments of the present application, the particle size of the electrolyte material may range from 250 nm to 350 nm.

[0094] In some embodiments of the present application, the particle size of the electrolyte material may range from 300 nm to 400 nm.

[0095] In some embodiments of the present application, the particle size of the electrolyte material may range from 300 nm to 350 nm.

[0096] That is, the particle size of the electrolyte material can be any one of 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, and 500nm, or any two of them. It should be noted that the thickness of the film layer is related to the speed of the fast reaction kinetics of the battery interface. If the thickness of the film layer is thicker, the internal resistance of the battery may be increased and the effective capacity of the battery may be reduced; if the thickness of the film layer is thinner, the electrochemical performance of the battery may be affected due to insufficient loading of LATP in the film layer, and there may also be safety hazards due to the battery not adapting to the volume change of the material.

[0097] In some embodiments of the present application, the thickness of the film layer may range from 6 μm to 8 μm.

[0098] It should be noted that the D50 particle size of the LATP powder and the thickness of the film layer are key parameters for improving the electrical performance of the battery. Therefore, the ratio of the D50 particle size of the LATP powder to the thickness of the film layer can be used as a key parameter to reflect the electrical performance of the battery.

[0099] In some embodiments of the present application, the ratio of the thickness of the membrane layer to the particle size of the electrolyte material ranges from 17.14 to 26.66, which can enable the battery to obtain better electrical performance.

[0100] In some embodiments of the present application, the foil material may include copper foil or aluminum foil.

[0101] It should be noted that the electrode of the present application can be applied to a positive electrode or a negative electrode. When applied to a positive electrode, the foil material can be aluminum foil. When applied to a negative electrode, the foil material can be copper foil.

[0102] In some embodiments of the present application, the active material layer may include a positive electrode membrane or a negative electrode membrane.

[0103] It should be noted that the electrode of the present application can be applied to a positive electrode or a negative electrode. When applied to a positive electrode, the active material layer can be a positive electrode membrane. When applied to a negative electrode, the active material layer can be a negative electrode membrane.

[0104] In some embodiments of the present application, the mass percentage of LATP in the bottom film layer is 91% to 97.9%, the mass percentage of the binder in the bottom film layer is 2% to 6%, and the mass percentage of the conductive agent in the bottom film layer is 0.1% to 3%; this is beneficial to ensure that LATP has a higher solid content in the bottom film layer, thereby improving the ion conduction effect; the binder in the above range of mass percentage can promote the generation of fiberization to form a network structure, which helps to enhance the structural stability of the electrode.

[0105] In some embodiments of the present application, the conductive agent includes but is not limited to conductive carbon black, conductive graphite, carbon nanotubes, vapor-grown carbon fibers, and the like.

[0106] In some embodiments of the present application, the binder includes but is not limited to polyvinylidene fluoride PVDF, polytetrafluoroethylene PTFE, polyolefins PP, PE, PEO, PPO or PDMS, etc. The binder plays a key role in the fiberization process. The above types of binders can promote the generation of fiberization to form a network structure, which helps to enhance the structural stability of the electrode and improve flexibility and mechanical strength.

[0107] In some embodiments of the present application, the weight average molecular weight of PTFE ranges from 4 million to 12 million.

[0108] In some embodiments of the present application, the weight average molecular weight of PTFE ranges from 2 million to 8 million. The higher the molecular weight of PTFE, the stronger its ability to undergo fiberization in the membrane layer.

[0109] In some embodiments of the present application, the preset temperature may be in the range of 140° C. to 200° C. The preset temperature is in the above range, which is greater than the glass transition temperature of the binder, and helps to promote the fiberization of the mixture formed by LATP, the conductive agent and the binder.

[0110] In some embodiments of the present application, the preset temperature may be any one of 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C or 200°C, or a range between any two of them.

[0111] In some embodiments of the present application, the preset shear speed may be in the range of 30 m / s to 40 m / s. Setting the shear speed in the above range is conducive to promoting the fiberization of the binder. If the shear speed is too high, the formed fiberized structure may be destroyed, and the binder may be over-sheared, which is not conducive to the formation and growth of fiberization.

[0112] In some embodiments of the present application, the preset shear speed may range from 35.5 m / s to 38.5 m / s.

[0113] Specifically, the preset shear speed may be any one of 30 m / s, 32 m / s, 34 m / s, 36 m / s, 38 m / s or 40 m / s, or a range between any two of them.

[0114] It should be noted that the positive electrode needs to have a higher shear rate than the negative electrode because the positive electrode powder is more difficult to fiberize, so a higher shear rate is required to provide a higher shear force.

[0115] In some embodiments of the present application, repeatedly rolling the fiberized powder includes: rolling the fiberized powder into an initial film sheet of the film layer; and then rolling the initial film sheet at a temperature of 140° C. to 200° C. to obtain the film layer.

[0116] It should be noted that the rolling process can help make the density of the membrane layer more uniform, reduce porosity, lower battery impedance, and increase ion conductivity, which is crucial to improving the performance of lithium-ion batteries.

[0117] The present application is described in detail below by means of specific examples, which are only partial examples of the present application and are not intended to limit the present application. The raw materials used in the following examples are all commercially available products unless otherwise specified.

[0118] Example 1

[0119] A lithium ion battery is manufactured by stacking a positive electrode, a negative electrode and a 12 μm thick diaphragm together in the order of "negative electrode-diaphragm-positive electrode-diaphragm-negative electrode".

[0120] Wherein, the positive electrode is prepared by the following method:

[0121] 1. Preparation of film layer:

[0122] 1) LATP, SP and PTFE are uniformly mixed in a mass ratio of 95:1:4 to obtain a mixture; wherein the D50 of the LATP particle size is 350 nm, and the weight average molecular weight of the PTFE is 6 million to 7 million;

[0123] 2) the mixture is then fiberized at 150° C. and a shear rate of 30 m / s to obtain a fiberized powder;

[0124] 3) The fiberized powder is pressed into an initial film sheet of the film layer at 80° C. by a hot roller press, and then the initial film sheet is repeatedly rolled at 150° C. to be thinned to 4 μm to obtain a film layer.

[0125] 2. Compounding the film layer with an aluminum foil having a thickness of 12 μm at a temperature of 150° C. by a roller press to obtain an LATP-primed aluminum foil;

[0126] 3. Preparation of positive electrode membrane:

[0127] The NCM811 positive electrode was mixed with SP and PTFE in a mass ratio of 95:2:3, and then fiberized at 180°C and a shear speed of 40m / s. The fiberized powder was pressed into a dry initial membrane at 80°C by a hot roller press, and the initial membrane was repeatedly rolled and thinned at 150°C to finally obtain a positive electrode membrane with a thickness of 55μm and a compaction density of 3.55g / cc.

[0128] 4. Compound the positive electrode film with the LATP-primed aluminum foil at 150°C by a hot roller press to obtain a positive electrode;

[0129] Wherein, the negative electrode is prepared by the following method:

[0130] 1. Preparation of film layer:

[0131] 1) LATP (using Li 1.4 Al0.4 Ti 1.6 (PO4)3), SP (manufacturer Swiss Temeco, brand Super P Li) and PTFE are uniformly mixed in a mass ratio of 94:1:5 to obtain a mixture; wherein the D50 particle size of the electrolyte material is 350nm;

[0132] 2) the mixture is then fiberized at 150° C. and a shear rate of 30 m / s to obtain a fiberized powder;

[0133] 3) The fiberized powder is pressed into an initial film sheet of the film layer at 80° C. by a hot roller press, and then the initial film sheet is repeatedly rolled at 150° C. to be thinned to 4 μm to obtain a film layer.

[0134] 2. Compounding the film layer with a copper foil having a thickness of 8 μm at a temperature of 150° C. by a roller press to obtain a copper foil after primer coating;

[0135] 3. Preparation of negative electrode membrane:

[0136] The graphite negative electrode was mixed with SP and PTFE in a mass ratio of 98:1:1, and then fiberized at 180°C and a shear speed of 30m / s. The fiberized powder was pressed into a dry initial membrane at 80°C by a hot roller press, and the initial membrane was repeatedly rolled and thinned at 150°C to finally obtain a negative electrode membrane with a thickness of 70μm and a compaction density of 1.6g / cc.

[0137] 4. The negative electrode film was compounded with the LATP-primed copper foil at 150°C by a hot roller press to obtain a negative electrode.

[0138] Example 2

[0139] The difference from Example 1 is that the thickness of the film layer in the positive electrode and the negative electrode is 6 μm; the appearance of the composite foil with film layer in Example 2 is shown in FIG. Figure 4 shown.

[0140] Example 3

[0141] The difference from Example 1 is that the thickness of the film layer in the positive electrode and the negative electrode is 8 μm.

[0142] Example 4

[0143] The difference from Example 1 is that the thickness of the film layer in the positive electrode and the negative electrode is 10 μm.

[0144] Example 5

[0145] The difference from Example 1 is that the thickness of the film layer in the positive electrode and the negative electrode is 12 μm.

[0146] Example 6

[0147] The difference from Example 2 is that the D50 particle size of the LATP in the film layers of the positive electrode and the negative electrode is 200 nm.

[0148] Example 7

[0149] The difference from Example 2 is that the D50 particle size of the LATP in the membrane layers of the positive electrode and the negative electrode is 250 nm.

[0150] Example 8

[0151] The difference from Example 2 is that the D50 particle size of the LATP in the membrane layers of the positive electrode and the negative electrode is 300 nm.

[0152] Example 9

[0153] The difference from Example 2 is that the D50 particle size of the LATP in the membrane layers of the positive electrode and the negative electrode is 400 nm.

[0154] Example 10

[0155] The difference from Example 2 is that the D50 particle size of the LATP in the film layers of the positive electrode and the negative electrode is 450 nm.

[0156] Embodiment 11

[0157] The difference from Example 2 is that the D50 particle size of the LATP in the membrane layer of the positive electrode and the negative electrode is 500 nm.

[0158] Example 12

[0159] The difference from Example 3 is that the D50 particle size of the LATP in the film layers of the positive electrode and the negative electrode is 200 nm.

[0160] Example 13

[0161] The difference from Example 3 is that the D50 particle size of the LATP in the film layers of the positive electrode and the negative electrode is 250 nm.

[0162] Embodiment 14

[0163] The difference from Example 3 is that the D50 particle size of the LATP in the membrane layer of the positive electrode and the negative electrode is 300 nm.

[0164] Embodiment 15

[0165] The difference from Example 3 is that the D50 particle size of the LATP in the membrane layers of the positive electrode and the negative electrode is 400 nm.

[0166] Example 16

[0167] The difference from Example 3 is that the D50 particle size of the LATP in the membrane layer of the positive electrode and the negative electrode is 450 nm.

[0168] Embodiment 17

[0169] The difference from Example 3 is that the D50 particle size of the LATP in the membrane layer of the positive electrode and the negative electrode is 500 nm.

[0170] Comparative Example 1

[0171] The difference from Example 2 is that the film layers in the positive electrode and the negative electrode are prepared by a wet process, and the specific steps include:

[0172] Dissolve sodium carboxymethyl cellulose in deionized water to form an aqueous solution of sodium carboxymethyl cellulose, add the deionized water dispersion of LATP and mix well;

[0173] Then, a conductive agent SP, SBR and a surfactant are added in sequence and mixed evenly to obtain a membrane slurry; wherein the mass percentages of LATP, sodium carboxymethyl cellulose, conductive agent SP, SBR and surfactant are 92.84%: 1%: 1%: 5%: 0.16%; sodium carboxymethyl cellulose is selected from Daicel 2200, and the surfactant is selected from sodium sulfosuccinate diester, and the particle size D50 of LATP is 350nm; wherein the solid content in the membrane slurry is 28.43%, and the viscosity is 173mPa·s;

[0174] The film layer slurry is coated on an aluminum foil with a thickness of 12 μm by a coating machine, and a film layer with a thickness of 6 μm is obtained after drying.

[0175] Detection methods:

[0176] 1. Lithium battery electrode buckle charge and discharge test method:

[0177] The equipment uses a blue electric test cabinet, model M340A. A single-sided composite positive electrode is used for testing, where the negative electrode is cut into a disc with a diameter of 8.4mm, and the positive electrode is cut into a disc with a diameter of 14mm. Each electrode is weighed; then the electrode is placed in a vacuum oven and baked for 8 hours, the vacuum degree is 0.1MPa, the oven temperature of the positive electrode is 85℃, and the oven temperature of the negative electrode is 130℃; then the electrode is assembled with lithium sheets, diaphragms, gaskets, and electrolytes into CR2016 button batteries, and then the corresponding performance tests are carried out.

[0178] 1. The first week of charge and discharge test of negative electrode:

[0179] (1) Stand for 2h; (2) 0.1C constant current discharge, cut-off voltage 0.005V; (3) 0.09C constant current discharge, cut-off voltage 0.001V; (4) 0.08C constant current discharge, cut-off voltage 0.001V; (5) 0.07C constant current discharge, cut-off voltage 0.001V; (6) 0.06C constant current discharge, cut-off voltage 0.001V; (7) 0.05C constant current discharge, cut-off voltage 0.001V; (8) 0.04C constant current discharge, cut-off voltage 0.001V; (9) 0.03C constant current discharge, cut-off voltage 0.001V; (10) 0.02C constant current discharge, cut-off voltage 0.001V; (11) Stand for 15min; (12) 0.1C constant current charge, cut-off voltage 1.5V; (13) Stand for 10min; (14) End.

[0180] 2. Rate charge and discharge test steps of negative electrode:

[0181] (1) Stand for 2 h; (2) 0.1C constant current discharge, cut-off voltage 0.01 V; (3) 0.01V constant voltage discharge, constant voltage time 5 h; (4) Stand for 15 min; (5) 0.1C constant current charge, cut-off voltage 1.5 V; (6) Stand for 15 min; (7) 0.2C constant current discharge, cut-off voltage 0.01 V; (8) 0.01V constant voltage discharge, cut-off current 0.001 mA, or constant voltage time ≥ 7 h; (9) Stand for 15 min; (10) 0.2C constant current charge, cut-off voltage 1.5 V; (11) Stand for 15 min; (12) 0.2C constant current discharge, cut-off voltage 0. 01V; (13) 0.01V constant voltage discharge, cut-off current 0.001mA, or constant voltage time ≥5h; (14) stand for 15min; (15) 2C constant current charge, cut-off voltage 1.5V; (16) stand for 15min; (17) 1C constant current discharge, cut-off voltage 0.01V; (18) 0.01V constant voltage discharge, cut-off current 0.001mA, or constant voltage time ≥5h; (19) stand for 15min; (20) 0.2C constant current charge, cut-off voltage 1.5V; (21) stand for 15min; (22) 2C constant current discharge, cut-off voltage 0.01V; (23) end.

[0182] 3. First week charge and discharge test steps of positive electrode:

[0183] (1) Stand for 12 hours; (2) 0.1C constant current charging, cut-off voltage 4.3V; (3) Constant voltage charging at 4.3V, cut-off current 0.005C; (4) Stand for 10 minutes; (5) 0.1C constant current discharge, cut-off voltage 3.0V; (6) Stand for 10 minutes; (7) End.

[0184] 4. Positive electrode charge rate discharge test steps:

[0185] (1) Stand for 12 hours; (2) 0.1C constant current charging, cut-off voltage 4.3V; (3) Constant voltage charging at 4.3V, cut-off current 30μA; (4) Stand for 10 minutes; (5) 0.1C constant current discharge, cut-off voltage 3.0V; (6) Stand for 10 minutes; (7) 0.3C constant current charging, cut-off voltage 4.3V; (8) Constant voltage charging at 4.3V, cut-off current 30μA; (9) Stand for 10 minutes; (10) 0.3C constant current discharge, cut-off voltage 3.0V; (11) Stand for 10 minutes; (12) 0.3C constant current charging, cut-off voltage 4.3V; (13) Constant voltage charging at 4.3V, cut-off current 30μA; (14) Stand for 10 minutes; (15) 0.5C constant current discharge, cut-off voltage 3.0V; (16) Stand for 10 minutes; (17) 0.3C constant current charging, cut-off voltage 4.3V; (18) constant voltage charging at 4.3V, cut-off current 30μA; (19) stand for 10min; (20) 1C constant current discharge, cut-off voltage 3.0V; (21) stand for 10min; (22) 0.3C constant current charging, cut-off voltage 4.3V; (23) constant voltage charging at 4.3V, cut-off current 30μA; (24) stand for 10min; (25) 3C constant current discharge, cut-off voltage 3.0V; (26) stand for 10min; (27) 0.3C constant current charging, cut-off voltage 4.3V; (28) constant voltage charging at 4.3V, cut-off current 30μA; (29) stand for 10min; (30) 5C constant current discharge, cut-off voltage 3.0V; (31) stand for 10min; (32) end.

[0186] 2. Test method of electrode resistance:

[0187] The electrode resistance meter BER2500 produced by Yuanneng Technology was used for testing with double-sided electrodes. The size of the electrode was 50mm*150mm. If the test electrode was a positive electrode, the pressure was set to 25MPa; if the test electrode was a negative electrode, the pressure was set to 5MPa. 10 points were tested at equal intervals along the long side of the electrode, and the pressure holding time for each test point was 10s. Finally, the data of 10 test points were obtained, and the average of these data was taken to obtain the electrode resistance of the electrode.

[0188] 3. Test method for full battery electrical performance:

[0189] The following tests were performed using a CT3001A Blue Electric test cabinet:

[0190] 1. Normal temperature DCR test method:

[0191] 1.1. Detection method:

[0192] (1) Capacity calibration: charge to Vmax at 1C constant current and constant voltage, with a cut-off current of 0.05C; let stand for 5 min; discharge to Vmin at 1C constant current, let stand for 5 min; repeat the above steps twice, and record the second discharge capacity as Creal;

[0193] (2) Charge to Vmax at 1C constant current and constant voltage, with a cut-off current of 0.05C; let stand for 5 minutes;

[0194] (3) Discharge at 1C constant current for 30 min (50% SOC) and let stand for 30 min;

[0195] (4) Discharge at 2C for 10s, let stand for 40s, charge at 2C for 10s, let stand for 40s, and complete the test;

[0196] Note: The voltage sampling interval is 0.2s, the upper limit protection voltage is set to 4.5V, and the lower limit protection voltage is set to 1.5V.

[0197] 1.2. DCR calculation method:

[0198] (1) Calculation formula of discharge DCR:

[0199]

[0200] Where R dis Discharge DCR, V0 is the voltage value of the last 1s in the static process before discharge, V t is the voltage value at the 10th second of the discharge process, I dis is the discharge current.

[0201] (2) Calculation formula for charging DCR:

[0202]

[0203] Where R cha Charging DCR, V0 is the voltage value of the last 1s during the static process before charging, V t is the voltage value at the 10th second (check the second) of the charging process, I dis is the discharge current.

[0204] 2. Rate discharge test method:

[0205] (1) Charge to V at 0.5C constant current and constant voltage max , cut-off current 0.05C, stand for 10min; discharge at 0.2C constant current to V min , let stand for 10 minutes;

[0206] (2) Charge at 0.5C constant current and constant voltage to V max, cut-off current 0.05C, stand for 10min; discharge at 0.5C constant current to V min , let stand for 10 minutes;

[0207] (3)2.3 Charge at 0.5C constant current and constant voltage to V max , cut-off current 0.05C, stand for 10min; discharge at 1C constant current to V min , let stand for 15 minutes;

[0208] (4) Charge at 0.5C constant current and constant voltage to V max , cut-off current 0.05C, stand for 10min; discharge at 2C constant current to V min , let stand for 20 minutes;

[0209] (5) Charge to V at 0.5C constant current and constant voltage max , cut-off current 0.05C, stand for 10min; discharge at 3C constant current to V min , let stand for 30 minutes;

[0210] (6) Charge at 0.5C constant current and constant voltage to V max , cut-off current 0.05C, stand for 10min; discharge at 5C constant current to V min , let stand for 30 minutes;

[0211] (7) Charge at 0.5C constant current and constant voltage to V max , cut-off current 0.05C, stand for 10min; discharge at 7C constant current to V min , let stand for 35 minutes;

[0212] (8) Charge to V at 0.5C constant current and constant voltage max , cut-off current 0.05C, stand for 10min; discharge at 10C constant current to V min , let stand for 35 minutes.

[0213] 3. Rate charging test method:

[0214] (1) Charge to V at 0.2C constant current and constant voltage max , cut-off current 0.05C, stand for 10min; discharge at 0.5C constant current to V min , let stand for 10 minutes;

[0215] (2) Charge at 0.5C constant current and constant voltage to V max , cut-off current 0.05C, stand for 10min; discharge at 0.5C constant current to V min , let stand for 10 minutes;

[0216] (3) Charge to V with 1C constant current and constant voltage max, cut-off current 0.05C, stand for 15min; discharge at 0.5C constant current to V min , let stand for 10 minutes;

[0217] (4) Charge to V with 2C constant current and constant voltage max , cut-off current 0.05C, stand for 20min; discharge at 0.5C constant current to V min , let stand for 10 minutes;

[0218] (5) Charge to V at 3C constant current and constant voltage max , cut-off current 0.05C, stand for 30min; discharge at 0.5C constant current to V min , let stand for 10 minutes;

[0219] (6) Charge to V at 5C constant current and constant voltage max , cut-off current 0.05C, stand for 30min; discharge at 0.5C constant current to V min , let stand for 10 minutes;

[0220] (7) Charge to V at 7C constant current and constant voltage max , cut-off current 0.05C, stand for 30min; discharge at 0.5C constant current to V min , let stand for 10 minutes;

[0221] (8) Charge to V at 10C constant current and constant voltage max , cut-off current 0.05C, stand for 30min; discharge at 0.5C constant current to V min , let stand for 10 minutes.

[0222] 4. Low temperature discharge test method:

[0223] (1) Place the battery in a -20℃±2℃ environment for 4 hours, then discharge it at a constant current of 0.5C to the lower limit voltage, and record the discharge capacity. Take out the battery, place it at room temperature for 4 hours, and then fully charge it at a constant current and constant voltage of 0.5C, and then proceed to the next temperature test.

[0224] (2) Place the battery in a -10℃±2℃ environment for 4 hours, then discharge it at a constant current of 0.5C to the lower limit voltage, and record the discharge capacity. Take out the battery, place it at room temperature for 4 hours, and then fully charge it at a constant current and constant voltage of 0.5C, and then proceed to the next temperature test.

[0225] (3) Place the battery in an environment of 25℃±2℃ for 4 hours, then discharge it at a constant current of 0.5C to the lower limit voltage, record the discharge capacity, and complete the test.

[0226] 4. Full battery alternating current impedance (EIS) test method:

[0227] The Bio-Logic electrochemical workstation, model VSP-3e, was used. The voltage oscillation mode was adopted, the voltage amplitude was 10mV, and the test frequency range (high frequency to low frequency) was 10 5 Hz~0.03Hz. First adjust the battery to 50% SOC before testing.

[0228] 5. Full battery puncture test method:

[0229] The extrusion acupuncture machine from Dongguan Bell was used, model BE-6047-2T. The test method is as follows: Battery charging method: The battery is charged at 1C constant current and constant voltage to the upper limit cut-off voltage of the battery, and the cut-off current is set to 0.05C. After being left at 25℃±2℃ for 30 minutes, the test is carried out under the following conditions:

[0230] a) Needle puncture direction: Needle puncture perpendicular to the direction of the battery cell plate, or in the same direction as the battery cell is most susceptible to needle puncture in the vehicle layout;

[0231] b) Acupuncture form: steel needle Length: 100 mm;

[0232] c) Needle puncture speed: 300 mm / min;

[0233] d) Acupuncture degree: Acupuncture is stopped when the voltage reaches 0V or the deformation reaches 94mm;

[0234] e) Maintain for 10 minutes;

[0235] After completing the above test steps, observe the battery at the test environment temperature for 60 minutes, and then observe and record the battery status after the test. Judgment criteria: If the battery does not catch fire or explode after the test, it is judged as "passed", otherwise it is "failed".

[0236] Test results:

[0237] 1. Electrode performance and full battery test results of Example 2 and Comparative Example 1:

[0238] Table 1 shows the test results of the full battery electrical performance of Example 2 and Comparative Example 1:

[0239]

[0240] Table 2 Full battery puncture test results of Example 2 and Comparative Example 1

[0241]

[0242]

[0243] Combined with Example 2, Comparative Example 1 and Figure 5-6The test results show that under low rate charge and discharge conditions, the charge and discharge curves of Example 2 still have smaller polarization, indicating that the electrode of Example 2 with dry primer process has better kinetic performance than the electrode of Comparative Example 1 with wet primer process, which is reflected in the fact that the voltage of the discharge curve of the former is higher overall, and the voltage of the charge curve is lower overall. The average discharge voltage of the former is 3.623V, which is higher than the average discharge voltage of the latter 3.595V, indicating that the dry primer has a higher discharge voltage platform and energy density. Figure 6 By comparing the AC impedance curves, it can be seen that the primer electrode using the dry process has a significantly lower charge transfer impedance R ct , Figure 1 The conclusions were further confirmed.

[0244] Combining the test results of Example 2, Comparative Example 1 and Tables 1-2, it can be seen that the dry-primed battery of Example 2 has a lower DCR value, better rate performance and low-temperature discharge performance than the wet-primed battery of Comparative Example 1. This is because the film layer of Example 2 has a higher LATP content (95%) and a lower binder dosage (4%), while the LATP content in the film layer of Comparative Example 1 is only 92.84%, and the total dosage of binder and surfactant is also 6.16% higher. A higher LATP content can achieve a better ion conduction effect, and a lower binder, surfactant and other components that do not play an electronic conductivity and ion conductivity role can achieve a lower electrode resistance; in addition, there are also differences in the internal structures of the film layers of Example 2 and Comparative Example 1. In the film layer of Example 2, PTFE presents a fibrous network structure inside the film layer, which can connect the LATP particles together and basically does not affect the direct contact between the LATP particles, thereby facilitating the construction of the lithium ion channel network; while in the film layer of Comparative Example 1, sodium carboxymethyl cellulose will be wrapped on the surface of the LATP particles, blocking the direct contact between the particles, and the agglomeration of SBR and SP will further block the ion conduction between the particles, ultimately making the continuity of the lithium ion channel poor; therefore, the film layer of Example 2 has a lower DCR value, better rate performance and low-temperature discharge performance. In addition, Example 2 has a higher needle puncture pass rate than Comparative Example 1. This is because the film layer of Example 2 has better thickness uniformity and thus has better battery safety and consistency.

[0245] 2. Electrode performance and full battery test results of Examples 1 to 5:

[0246] Table 3 Positive electrode performance test results of Examples 1-5

[0247]

[0248] Table 4 Negative electrode performance test results of Examples 1-5

[0249]

[0250]

[0251] Table 5 Full battery performance test results of Examples 1-5

[0252]

[0253] Combining the test results of Examples 1-5 and Table 3, it can be seen that the difference between Examples 1-5 is that the thickness of the film layer is 4μm, 6μm, 8μm, 10μm, and 12μm, respectively. The first efficiency of the positive electrode with different thicknesses is between 92% and 93%, indicating that the thickness of the film layer has little effect on the first efficiency of the positive electrode. The first week capacity of the power-on shows a trend of first increasing and then decreasing with the increase of the thickness of the film layer. When the thickness is 6μm or 8μm, the first week capacity of the power-on reaches a peak of 214.6-214.7mAh / g. This result shows that a film layer that is too thin or too thick is not conducive to the first week capacity of the positive electrode. Therefore, there is an optimal value for the thickness of the film layer. This is because LATP itself is a good ion conductor. When the composite film layer on the foil is composited with the active material layer, the film layer and the active material layer will be embedded and combined with each other under the action of hot rolling composite, thereby improving the lithium ion transmission of the active material layer close to the side of the foil, and ultimately improving the electrode kinetics and reducing polarization, and improving the first week capacity of the power-on. As the thickness of the film layer increases, the degree of mutual embedding and bonding between it and the active material layer becomes higher, and the improvement effect on lithium ion transmission becomes more obvious. Therefore, when the thickness of the film layer increases from 4μm to 8μm, the capacity of the first week of charging shows an increasing trend. However, LATP itself is a solid oxide with poor electronic conductivity. A conductive agent is added to the film layer to make up for the defect of poor conductivity of LATP itself. However, as the thickness of the film layer increases further, the contact resistance between the active material layer and the foil will increase significantly, making it impossible for electrons to be transmitted between the active material layer and the foil, which ultimately leads to a decrease in electrical performance. When the thickness of the film layer increases from 8μm to 10μm, the capacity of the first week of charging decreases by 1.8mAh / g, the retention rate of the 3C / 0.3C discharge rate decreases by 5.7%, and the electrode resistance increases by 3.3mΩ; when the thickness of the film layer further increases to 12μm, the electrical properties of the electrode in all aspects also decrease further.

[0254] As can be seen from Table 4, the performance change law of the negative electrode is similar to that of the positive electrode. When the thickness of the film layer is 6μm or 8μm, the electrical performance of the negative electrode is optimal. However, the first effect of the negative electrode will continue to decrease with the increase of the thickness of the film layer. This is because PTFE itself will consume active lithium in side reactions at the low potential of the negative electrode. As the thickness of the film layer increases, the content of PTFE will also increase, resulting in the intensification of side reactions. Therefore, the thickness of the film layer should not be too thick. When the thickness is between 4μm and 8μm, the decrease in the first effect is small, and when the thickness is 6μm or 8μm, the optimal electrode performance can be obtained.

[0255] It can be seen from Table 5 that when the thickness of the film layer is 6μm, the battery has the lowest DCR value, better rate performance and low-temperature discharge performance. When the thickness of the film layer increases from 8μm to 10μm, the DCR value increases significantly, and the rate charging performance and negative 20 degree discharge performance also decrease significantly, indicating that the thickness of the film layer is preferably 6μm, which can obtain the best electrode performance.

[0256] Based on the above examples, it can be seen that the ratio of the thickness of the membrane layer to the particle size of the electrolyte material is in the range of any one of 11.43, 17.14, 22.86, 28.57, and 34.29 or in the range between any two of them. 3. Test results of the electrode performance and full battery of Examples 2 and 6-11:

[0257] Table 6 Positive electrode performance test results of Example 2 and Examples 6-11

[0258]

[0259] Table 7 Negative electrode performance test results of Example 2, Examples 6-11

[0260]

[0261] Table 8 Full battery performance test results of Example 2, Examples 6-11

[0262]

[0263]

[0264] Based on the above embodiments 6 to 11, it can be known that the ratio of the thickness of the membrane layer to the particle size of the electrolyte material ranges from any one of 30.00, 24.00, 20.00, 17.14, 15.00, 13.33, and 12.00 or a range between any two of them.

[0265] Combining the test results of Example 2, Example 6-11 and Table 6-8, it can be seen that the difference between Example 2 and Example 6-11 is that the D50 particle size of the LATP powder is different, and the first efficiency of the positive electrode is between 92% and 93%, indicating that the particle size of the LATP powder has little effect on the first efficiency of the positive electrode. The first week capacity of the power-on shows a trend of first increasing and then decreasing with the increase of the LATP particle size. When the particle size is between 250 and 350 nm, the first week capacity of the power-on reaches a high level of 214.7 to 215.3 mAh / g; when the LATP particle size exceeds this range, the first week capacity of the power-on shows a more obvious downward trend, indicating that the LATP particle size is too small or too large, which is not conducive to the performance of the positive electrode capacity. This is because if the LATP particle size is large, its specific surface area will be small, which will reduce the gain effect of LATP on lithium ion conduction, but if the LATP particle size is too small, it will also lead to a large contact resistance between LATP particles and between LATP and the active material, which will increase the resistance of the film layer and the overall resistance of the electrode, and ultimately reduce the electrical performance. Therefore, the particle size range is preferably 250-350nm, at which point the electrode first-week capacity and 3C / 0.3C discharge retention rate are both at a high level. As shown in Table 7, the change law of the electrical properties of the negative electrode is the same as that of the positive electrode, and the LATP particle size is preferably 250nm-350nm. As shown in Table 8, the particle size range of LATP is between 250nm-350nm, and the full battery has a lower DCR value and optimal rate performance and low-temperature discharge performance.

[0266] In summary, when the thickness of the membrane layer is 6μm and the D50 particle size of the LATP powder is 250-350nm, the dry solid electrolyte electrode and the full battery have excellent electrical properties.

[0267] 4. Test results of the electrode performance and full battery of Examples 3 and 12-17:

[0268] Table 9 Positive electrode performance test results of Example 3 and Examples 12-17

[0269]

[0270] Table 10 Negative electrode performance test results of Example 3, Examples 12-17

[0271]

[0272]

[0273] Table 11 Full battery performance test results of Example 3 and Examples 12-17

[0274]

[0275] Based on the above-mentioned embodiments 12 to 17, it can be known that the ratio of the thickness of the membrane layer to the particle size of the electrolyte material ranges from any one of 40.00, 32.00, 26.67, 22.86, 20.00, 17.78, 16.00 or a range between any two of them.

[0276] Combining the test results of Example 3, Examples 12-17 and Tables 9 to 11, it can be seen that based on the performance such as the first-week capacity and electrode resistance, when the thickness of the film layer is 8μm, the D50 particle size of the LATP powder is preferably 300nm-400nm to ensure the optimal electrical performance of the battery.

[0277] In summary, when the film thickness is 6μm to 8μm, the optimal D50 particle size range of LATP powder is 300nm to 350nm, and the positive electrode, negative electrode and full battery have the best electrical performance.

[0278] The technical solutions provided by the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of ​​the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A current collector, characterized in that: The current collector comprises: A foil having two surfaces disposed opposite to each other; A film layer attached to at least one surface of the foil; The membrane layer includes an electrolyte material, a first conductive material and a first adhesive material, and the membrane layer is at least formed by combining the electrolyte material, the first conductive material and the first adhesive material in a dry state.

2. The current collector according to claim 1, characterized in that: The particle size of the electrolyte material ranges from 200 nm to 500 nm; and / or The thickness of the film layer ranges from 4 μm to 12 μm; and / or The ratio of the thickness of the membrane layer to the particle size of the electrolyte material is in the range of 8 to 60; and / or: The electrolyte material is lithium titanium phosphate; and / or The chemical formula of the electrolyte material is Li 1.4 Al 0.4 Ti 1.6 (PO4)3; and / or In the membrane layer, the mass percentage of the electrolyte material ranges from 91% to 97.9%.

3. The current collector according to any one of claims 1 to 2, characterized in that: The film layer is bonded to the foil by rolling at a first predetermined temperature.

4. The current collector according to any one of claims 1 to 2, characterized in that: The first conductive material is selected from one or more of conductive carbon black, conductive graphite, carbon nanotubes, and vapor-grown carbon fibers; and / or The first bonding material is selected from one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polyethylene oxide, polyphenylene ether or polydimethylsiloxane.

5. An electrode, characterized in that: A current collector comprising any one of claims 1 to 4.

6. The electrode according to claim 5, characterized in that: The electrode further comprises: The active material layer is attached to the side of the film layer away from the foil.

7. The electrode according to claim 6, characterized in that: The active material layer is formed by combining raw materials thereof in a dry state; the active material layer is combined onto the current collector by rolling at a second preset temperature.

8. The electrode according to claim 7, characterized in that: The active material layer includes an active material, a second conductive material and a second bonding material.

9. The electrode according to claim 8, characterized in that: The active material is selected from one or more of natural graphite, artificial graphite, silicon carbon / graphite mixture, silicon oxide / graphite mixture, lithium titanate, hard carbon, soft carbon, activated carbon, lithium battery ternary material, lithium iron phosphate, lithium cobalt oxide, sodium battery layered oxide, sodium battery polyanion compound, sodium battery Prussian blue analogue; and / or The second conductive material is selected from one or more of conductive carbon black, conductive graphite, carbon nanotubes, and vapor-grown carbon fibers; and / or The second bonding material is selected from one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polyethylene oxide, polyphenylene ether or polydimethylsiloxane.

10. A method for preparing a current collector, characterized in that: The preparation method of the current collector comprises: Providing a film layer; Provide foil; attaching the film layer to the surface of the foil; The membrane layer includes an electrolyte material, a first conductive material and a first adhesive material, and the membrane layer is at least formed by combining the electrolyte material, the first conductive material and the first adhesive material in a dry state.

11. The method for preparing the current collector according to claim 10, Features: Wherein, providing the film layer comprises: The mixed electrolyte material, the first conductive material and the first bonding material are subjected to a fiberizing treatment at a third preset temperature and a preset shearing speed to obtain a fiberized powder; The fiberized powder is rolled to obtain the film layer.

12. The method for preparing a current collector according to claim 11, characterized in that: The third preset temperature ranges from 40°C to 200°C; the preset shear speed ranges from 30m / s to 40m / s.

13. The method for preparing a current collector according to claim 12, characterized in that: in, The step of attaching the film layer to the surface of the foil material comprises: The film layer is bonded to the surface of the foil by rolling at a fourth preset temperature.

14. The method for preparing a current collector according to claim 13, characterized in that: The fourth preset temperature ranges from 100°C to 180°C.

15. A secondary battery, characterized in that: The secondary battery comprises the current collector according to any one of claims 1 to 4, or comprises the electrode according to any one of claims 6 to 9, or comprises the current collector prepared by the preparation method according to any one of claims 10 to 14.